2019
DOI: 10.1111/jpn.13198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum on the intestinal morphology, intestinal barrier function and microbiota composition of suckling piglets

Abstract: This study investigated the effect of Lactobacillus plantarum strain 299v on gut health in suckling piglets. Sixty newborn piglets were assigned to control and probiotic treatments, with three litters per treatment (ten piglets/litter). From days 1 to 20 of life, piglets were orally administered a placebo of 0.1% peptone or 1.0 ×  1010 CFU L. plantarum 299v daily. Six piglets per treatment were sacrificed on day 20, and intestinal tissues (including duodenum, jejunum, ileum and colon) and the intestinal conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
(72 reference statements)
4
19
0
1
Order By: Relevance
“…It means that L.casei treatment may increase the antimicrobial-peptides gene expression. Similar results were shown in some studies and indicated that Lactobacillus strain treatment increased the mRNA abundance of porcine β-defensin 2 (pBD2) and pBD3 in the piglet's jejunum and ileum (Zhang et al, 2011;Wang Q. et al, 2019). In a time series analysis of antimicrobial peptide expression, we found that the most antimicrobial peptide gene in GO terms which enriched significantly by DEGs was upregulated within days 10 with L.casei treatment.…”
Section: Discussionsupporting
confidence: 89%
“…It means that L.casei treatment may increase the antimicrobial-peptides gene expression. Similar results were shown in some studies and indicated that Lactobacillus strain treatment increased the mRNA abundance of porcine β-defensin 2 (pBD2) and pBD3 in the piglet's jejunum and ileum (Zhang et al, 2011;Wang Q. et al, 2019). In a time series analysis of antimicrobial peptide expression, we found that the most antimicrobial peptide gene in GO terms which enriched significantly by DEGs was upregulated within days 10 with L.casei treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Post-weaning piglets received L. plantarum in the diet had improvement in the regulation of tight junction proteins (claudin-1, occludin and zona-occluden-1 (ZO-1)) concurrently with the strengthening of epithelium and modulating gut microbiota [55]. In suckling piglets, L. plantarum administration in the diet upregulated the jejunal OCLD, ileal ZO-1 and jejunal and the ileum of porcine B-defensin with an improvement of intestinal morphology and increment of relative abundance of phyla Firmicutes and Actinobacteria and genus Lactobacillus [56]. Orally supplemented mice with L. plantarum-fermented milk modulated the intestinal barrier function and ameliorated the enteric infection by Salmonella through the evaluation of intestinal permeability and histopathology [57].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial colonization plays an important role in intestinal homeostasis and metabolism (Turnbaugh et al 2009;Wang et al 2019). Probiotics, alive microbial agents, have been demonstrated to confer a beneficial role in the gut health via controlling intestinal pathogens and regulating intestinal microbiota composition and immune function (Schoster et al 2013;Sokale et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2009; Wang et al . 2019). Probiotics, alive microbial agents, have been demonstrated to confer a beneficial role in the gut health via controlling intestinal pathogens and regulating intestinal microbiota composition and immune function (Schoster et al .…”
Section: Introductionmentioning
confidence: 99%